2016
DOI: 10.5507/bp.2016.042
|View full text |Cite
|
Sign up to set email alerts
|

The safety and efficacy of Heparin and Nadroparin compared to placebo in acute ischemic stroke - pilot study

Abstract: Aims. This study aimed to compare the efficacy and safety of heparin and nadroparin in order to provide an additional therapeutic option for patients with acute ischemic stroke in, whom systemic thrombolysis was excluded, or thrombectomy could not be performed. Methods. We describe a prospective randomized double-blind placebo-controlled pilot study in acute ischemic stroke. The therapeutic window was between 4.5 and 24 h after the onset of stroke. During the first 24 h of treatment, the patients divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Heparin, a commonly prescribed anticoagulant, is used in ischemic stroke prevention. Studies focusing on the efficacy and safety of heparin alone or in combination therapies have demonstrated that heparin is safe and effective in ischemic attacks ( Yi et al, 2014 ; Dluha et al, 2016 ); however, novel therapeutics are becoming more promising and could soon be implemented more regularly in favor to traditional heparin treatment ( Douketis et al, 2015 ; Han et al, 2015 ). The ontology terms that were suggestively associated with ASB10 and TTC37 included signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…Heparin, a commonly prescribed anticoagulant, is used in ischemic stroke prevention. Studies focusing on the efficacy and safety of heparin alone or in combination therapies have demonstrated that heparin is safe and effective in ischemic attacks ( Yi et al, 2014 ; Dluha et al, 2016 ); however, novel therapeutics are becoming more promising and could soon be implemented more regularly in favor to traditional heparin treatment ( Douketis et al, 2015 ; Han et al, 2015 ). The ontology terms that were suggestively associated with ASB10 and TTC37 included signal transduction.…”
Section: Discussionmentioning
confidence: 99%